Volar Plate-Suture Fixation in the Treatment of Volar Rim Fractures of the Distal Radius - Carney, John; Bigach, Stephen; Goedderz, Cody; Gerlach, Erik; Marx, Jeremy; Kalainov, David (Journal of Wrist Surgery, 2023)
Background The purpose of this study was to describe the volar plate-suture fixation technique for augmented repair of volar rim fractures of the distal radius and to report clinical outcomes and radiographic findings.Materials and Methods Twenty-one patients treated with volar plate-suture fixation were retrospectively reviewed. Outcomes of interest included pain, joint motion, grip strength, surgical complications, additional surgeries, and radiographic parameters.Results Final follow-up office visits from surgery averaged 30.8 weeks (range 6–175 weeks). There was no report of residual wrist pain in most cases. Forearm and wrist motion measurements were within functional ranges and grip strength measurements averaged 63 ± 21% of the contralateral hand. There were no cases of infection, wound dehiscence, nerve injury, or nonunion. Hardware removal was performed in four patients for wrist pain attributed to the fixation implant(s). One patient underwent a wrist fusion for treatment of painful traumatic wrist arthritis. Failure of the fracture fixation construct to hold the carpus occurred in two patients. Changes in radiocarpal and intercarpal angles averaged less than 4 degrees and loss of articular reduction averaged less than 1 mm, although with relatively high standard deviations.Conclusion Suture fixation of volar rim fractures of the distal radius may be a useful technique in augmenting volar plate fracture fixation. Some loss of early postoperative fracture alignment should be expected.Level of Evidence IV, case series.
Keywords: distal radius fracture; volar rim distal radius; watershed line; volar plate; suture fixation; distal radius; wrist; fracture; volar rim